Early deaths from childhood cancer in Germany 1980-2016. (April 2020) - Becker, Cornelia; Graf, Norbert; Grabow, Desiree; Creutzig, Ursula; Reinhardt, Dirk; Weyer-Elberich, Veronika; Spix, Claudia; Kaatsch, Peter
Highlights: There are still children dying shortly after cancer diagnosis. The risk for early death in Germany has decreased from 2.6% in the 1980s to 0.6% in the 2010s. Infants were at higher risk than older children (3.1% of infants with cancer died early). Children with AML are especially vulnerable (5.5% of children with AML died early). Abstract: Background: Even though the survival of childhood cancer has improved over the last decades, there are still children dying shortly after diagnosis. The aim of the study is to add to understanding of the reasons for deaths shortly after date of diagnosis. Methods: Using data of the population-based German Childhood Cancer Registry (cancer below 15 years of age diagnosed between 1980 and 2016), we compared characteristics of 671 children with cancer who died within 30 days of diagnosis to 53, 649 patients with childhood cancer who survived longer. In addition to a descriptive analysis, we used logistic regression with multivariable fractional polynomials to describe the relationship between early death with age at diagnosis and year of diagnosis. Results: The number of early death cases and the risk of early death have decreased considerably since 1980 (2.6% of study population in 1980-89 to 0.6% in 2010-16). Children under one year of age were at highest early death risk (odds ratio = 4.10, 95% confidence interval: 3.32–5.05 compared to 7-year-old patients). These results are similar to results from other studies. Moreover, children with acute myeloid leukemia and hepatic tumors had a higher early death risk, children with acute lymphoid leukemia a lower risk compared to patients with central nervous system tumors used as a reference group. Conclusion: Even though the risk for early death has declined overall with advances in diagnosis and therapy, special attention needs to be paid to infants and children with AML and hepatic tumors, who are especially at risk.